(untitled) (Лучшие интеллектуальные исследования, 2025)
The human mind possesses such immense power that it can, at one and the same time, or at some point, vividly recreate what it perceived through its senses. Often, it’s not a specific person or object that’s remembered, but rather situations. It is through these situations—emotions—that the main character is revived in one’s memory. Lev Tolstoy’s story is also structured upon such memories and imaginations.